Evaluasi Pelayanan Publik di Pelabuhan Roro Dompak Provinsi Kepulauan Riau - Susanto, Pamella Dwi Ariyanti; Samin, Rumzi; Subiyakto, Rudi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The service standards for the Roro Dompak port Kepulauan Riau Province are the parameters used as guidelines for the implementation of services and the objectivity of the criteria for assessing the quality of services to the community so that there is guidance on the obligations and promises of organizers to stakeholders in the context of quality, fast, easy, affordable and measurable services. The aim of the research is to analyze the evaluation of Public Services at Roro Dompak port Kepulauan Riau Province. Qualitative Research Method with primary data collection such as closed interviews and secondary data obtained from the Kepulauan Riau Province Transportation Service. Data analysis uses triangulation techniques and uses grand theory based on two approaches: process-oriented evaluation and results-based evaluation. Process-oriented evaluation focuses on the process of providing public services, including accountability, responsibility and responsiveness. Results-based evaluation focuses on public service outcomes, including effectiveness, economics, and efficiency. The research results show that the Roro Dompak port Kepulauan Riau Province has several strengths and weaknesses in providing public services to the community. Its advantages include its strategic location, adequate basic facilities and efficient operations. However, the weaknesses are limited capacity, inadequate infrastructure, and lack of transparency. This study also identified several areas that need to be improved, including increasing port capacity, improving infrastructure, and increasing transparency and accountability. Additionally, the study suggests that ports should focus on improving their responsiveness to community needs, increasing effectiveness in providing services, and reducing costs. Overall, this study provides a comprehensive evaluation of the public service performance of Roro Dompak Port and highlights areas that need improvement to increase its effectiveness in providing public services to the community Kepulauan Riau Province.